2007
DOI: 10.1111/j.1467-8624.2007.01071.x
|View full text |Cite
|
Sign up to set email alerts
|

Hindsight Bias and Developing Theories of Mind

Abstract: Although hindsight bias (the ''I knew it all along'' phenomenon) has been documented in adults, its development has not been investigated. This is despite the fact that hindsight bias errors closely resemble the errors children make on theory of mind (ToM) tasks. Two main goals of the present work were to (a) create a battery of hindsight tasks for preschoolers, and (b) assess the relation between children's performance on these and ToM tasks. In two experiments involving 144 preschoolers, 3-, 4-, and 5-year o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 81 publications
4
45
0
Order By: Relevance
“…The results also suggested that the children believed, very frequently, and consistent with Hypothesis 2, they knew the correct answers all along. Whether their claim that they knew the answers all along was a pure hindsight bias, as has previously been demonstrated in children (Bernstein, Atance, Meltzoff, & Loftus, 2007) or whether it was an indication that they really did know, is the issue that is investigated in the next two experiments.…”
Section: Discussionmentioning
confidence: 95%
“…The results also suggested that the children believed, very frequently, and consistent with Hypothesis 2, they knew the correct answers all along. Whether their claim that they knew the answers all along was a pure hindsight bias, as has previously been demonstrated in children (Bernstein, Atance, Meltzoff, & Loftus, 2007) or whether it was an indication that they really did know, is the issue that is investigated in the next two experiments.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the magnitude of the bias remained stable from ages three to five in both experiments. In a pair of follow-up experiments, Bernstein and colleagues found mixed evidence for a developmental decline in hindsight bias between the ages of three and five (Bernstein, Atance, Meltzoff, & Loftus, 2007). Hence, the data on whether there are developmental changes in the magnitude of hindsight bias across the preschool period are limited and somewhat mixed.…”
Section: Changes In Hindsight Bias Across Developmentmentioning
confidence: 99%
“…Interestingly, some cognitive abilities improve from young to middle adulthood followed by a decline in late adulthood (Kaufman, 2001;Thornton & Dumke, 2005). Researchers have investigated such nonlinear development trajectories of theory of mind (see Bernstein, Thornton, & Sommerville, 2011b), a social cognitive ability that is significantly correlated with HB (Bernstein, Atance, Meltzoff, & Loftus, 2007), but no work to date has implemented this approach in the HB literature.…”
Section: Limitations and Future Researchmentioning
confidence: 99%